Research on Train Visualization of Different Resolution in TCS Simulation - Ye Deng; Qianxiang Zhou; Weining Fang (Institute of Advanced Engineering and Science, 2013)
Train control system is to control the velocity and the distance between trains in the railway and to protect the safe and high efficiency of train running. An ideal train control system testing and simulation platform should simulate the real railway operating environment and the train running. There are different requirements for the train visualization in the train control system testing and simulation platform. According to the specific analysis of the train running behavior and multiresolution theory, this paper raised the train visualization modeling of different resolution. Meanwhile the aggregation and disaggregation process between different resolution models were analyzed in detail. After all, the availability of this method was certified by 3D train simulation cases. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1911